2002
DOI: 10.1161/hy0202.103821
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intrarenal Angiotensin II in Hypertension

Abstract: Abstract-Intrarenal angiotensin II (Ang II) is regulated by several complex processes involving formation from both systemically delivered and intrarenally formed substrate, as well as receptor-mediated internalization. There is substantial compartmentalization of intrarenal Ang II, with levels in the renal interstitial fluid and in proximal tubule fluid being much greater than can be explained from the circulating levels. In Ang II-dependent hypertension, elevated intrarenal Ang II levels occur even when intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
331
1
5

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 342 publications
(346 citation statements)
references
References 99 publications
9
331
1
5
Order By: Relevance
“…This effect was blocked by either saralasin or losartan indicating that this effect also involves AT1 receptor activation [68]. These findings, together with the demonstration that AT receptors are present on the luminal membranes of distal nephron segments [22,69] indicate that luminal Ang II plays an important role in the regulation not only of proximal reabsorption rate but also of distal tubular reabsorptive function [52]. Peti-Peterdi et al [70] demonstrated that Ang II directly stimulates epithelial sodium channel activity in the cortical collecting duct via AT1R.…”
Section: Tubular Function Of Ras Angiotensin IImentioning
confidence: 85%
See 3 more Smart Citations
“…This effect was blocked by either saralasin or losartan indicating that this effect also involves AT1 receptor activation [68]. These findings, together with the demonstration that AT receptors are present on the luminal membranes of distal nephron segments [22,69] indicate that luminal Ang II plays an important role in the regulation not only of proximal reabsorption rate but also of distal tubular reabsorptive function [52]. Peti-Peterdi et al [70] demonstrated that Ang II directly stimulates epithelial sodium channel activity in the cortical collecting duct via AT1R.…”
Section: Tubular Function Of Ras Angiotensin IImentioning
confidence: 85%
“…The intrarenal content of Ang II is not distributed in a homogenous manner but is compartmentalized in both a regional and segmental manner [52]. It has been reported that Ang II is present at high concentrations in renal interstitial fluid (RIF) thus contributing to the disproportionately high total Ang II levels in the kidney [52].…”
Section: Renal Interstitial Function Of Angiotensin IImentioning
confidence: 99%
See 2 more Smart Citations
“…The renin-angiotensin system plays an important role in blood pressure regulation and electrolyte homeostasis [5,[13][14][15]. In recent years, the focus of interest on the role of the reninangiotensin system in the regulation of arterial pressure and in the pathophysiology of hypertension has changed to a main emphasis on the role of the local/tissue renin-angiotensin systems in specific tissues [4].…”
Section: Introductionmentioning
confidence: 99%